POTENSI AIR RENDAMAN DAUN TEMBAKAU (Nicotiana tabacum) SEBAGAI BIOINSEKTISIDA KECOA (Periplaneta americana) - Ali, Isman Norianza; Ngadino, Ngadino; Suryono, Hadi (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2020)
Cockroaches are animals in residential areas that act as vectors of diseases, including cholera, typhus, dysentery and diarrhea, and are often found in a common public places. Tobacco (Nicotiana tabacum) contains nicotine so that it is a type of plant that can be used as a bio-insecticide to control insects.The experiment used a pretest-posttest control group design, with 9 replications. The test material used was tobacco leaf (Nicotiana tabacum) immersion water with immersion length variations of 2, 4, and 6 days. The cockroach being used was 810 Periplaneta americana obtained from residential areas. The data obtained were analyzed using the Oneway ANOVA test, Least Square Difference (LSD) and probit analysis.The results suggested that the highest percentage of cockroach (Periplaneta americana) mortality was in the use of 6 days immersed tobacco, by 32%. The results of the statistical analysis suggested a significant difference (p-Value = 0.000) in the treatment and control groups. However, there were no significant differences between treatment groups (p-value = 0.285). While the results of the probid analysis acquire the LD50 at 2.925% concentration.Immersed Tobacco leaf (Nicotiana tabacum) can be used as an alternative to bio-insecticides in cockroach control (Periplaneta americana). Further research is necessary to obtain significant results, in terms of variations in treatment, variations in contact time, and homogeneous test materials.Â